Bryozoen aus dem Nordatlantik und dem Englischen Kanal - D'Hondt, Jean-Loup (Bornträger, 1979)
Taxonomical study of the Bryozoa collected during the cruises of R. V. "Meteor" near the French coast (Atlantic and Channel) and the coastline of Mauritania. First indications of Arachnoidea annosciae n'HONDT and GERACI, 1976, Onychocella antiqua (BUSK, 1858) and Cribrilaria flabellifera (KIRKPATRICK, 1888) in the temperate region of the North Atlantic.